ANALISIS PEMANFAATAN SUMBER BELAJAR OLEH GURU SOSIOLOGI DI KELAS XI IPS 1 SMA NEGERI 2 SUNGAI RAYA KABUPATEN KUBU RAYA - Ayu, Nelli; Budjang A, Gusti; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to know 1). Types of Learning Resources Utilized Sociology Teachers in Class XI IPS 1 SMA Negeri 2 Sungai Raya Kabupaten Kubu Raya. 2). Learning Resources are in Use Sociology Teachers in Class XI IPS 1 SMA Negeri 2 Sungai Raya Kabupaten Kubu Raya Varied or not. This research is a qualitative research. Data collection techniques in this study is to use observation techniques, interviews, and documentary studies. While the data collection tools used are interview guides, observation guides, documents in the form of; notebook Â and archives. The results showed that the utilization of learning resources of sociology teacher of SMA Negeri 2 Sungai Raya Kabupaten Kubu Raya was less varied and frequency of utilization of various learning resources in the learning process was very rare. Selection of learning resources conducted by teachers is appropriate, but teachers must consider the criteria of learning resources that can increase student learning motivation in the classroom because the motivation of student learning in the classroom is still very less, teachers still often use the conventional learning model and fixed on one type of learning resources.Â Keywords: Utilization of Learning Resources, Teachers, Senior High School